BASICS ENGLISH GUARANTEE IN EFFORTS TO INCREASE THE ABILITY OF BIDIKMISI IAI AS'ADIYAH SENGKANG STUDENTS - Yusuf Razak; Satriani Satriani (Jurnal Abdimas Indonesia, 2021)
The quality of English instruction in Indonesia is not uniformly spread across the country. Those in big cities are more likely to receive qualified English instruction than students in rural areas. Bidikmisi kids do not have access to additional English learning resources, despite the fact that they require them. Finally, because English proficiency is so vital, their competition is low. As a result, Bidikmisi pupils' basic English skills must be enhanced in order to be more competitive. Basic English Training is provided to Bidikmisi students at IAI As'adiyah Sengkang who need it the most as part of this program. Aside from the pretest and post-test, 12 meetings were held. The results suggest that Bidikmisi students' basic English skills have improved. However, they must be persistent in their efforts to improve their knowledge in order to greatly boost their competency. It may be concluded that the basic English training program for Bidikmisi pupils aids in the development of human resource capabilities in the English field.